The Problem of Subject Access to Visual Materials - Heather P. Jespersen; John Kresten Jespersen (Jiàoyù zīliào yǔ túshūguǎn xué, 2004)
This article discusses the problem of giving subject access to works of art. We survey both concept-based and content-based access by computers and by indexers/catalogers respectively, as well as issues of interoperability, database and indexer consistency, and cataloging standards. The authors, both of whom are trained art historians, question attempts to mystify fine art subject matter by the creation of clever library science systems that are executed by the naive. Only when trained art historians and knowledgeable catalogers are finally responsible for providing subject access to works of art, will true interoperability and consistency happen.